Analisis Pemahaman Akad Qordh pada Pinjaman Multiguna di KSPPS Guna Lestari Cabang Troso - Siti Kumairoh; Wahidullah; Zahrotun Nafisah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the understanding of KSPPS Guna Lestari Jaya members regarding the qordh contract in multipurpose loans and the efforts made by the cooperative to improve this understanding. The qordh contract is an interest-free loan contract which is one of the superior products of sharia cooperatives, but members' understanding of this concept is still limited. Based on the results of the study, it was found that although most members understand that the qordh contract is an interest-free loan, they still do not understand the provisions and mechanisms for its repayment. KSPPS Guna Lestari Jaya has made various educational efforts and utilized social media as information material to improve members' understanding. Although this program is less effective, there are still obstacles related to time and lack of interest from members to understand. This study suggests that cooperatives continue to develop flexible technology-based education methods so that they are more easily accessible to members. Thus, it is hoped that members' understanding of the qordh contract will increase and more transparent and fair transactions will be created.